Rapid Bone Healing after Intentional Replantation of a Molar with Apical Actinomycosis - Asgary, Saeed; Roghanizadeh, Leyla (Iranian Endodontic Journal, 2019)
Actinomycosis is a rare lesion of the jaws and may present as periapical pathosis; therefore, it is essential to be correctly diagnosed and managed. This case presentation describes management of a tooth with a symptomatic apical periodontitis caused by Actinomyces species supplemented with medicine prescription. A woman was referred for endodontic management of tooth #19. The tooth had a history of previous nonsurgical endodontic retreatment. Clinically, the tooth was very sensitive to percussion. Radiographic evaluation showed a large periapical lesion. Intentional replantation (IR) was planned. The tooth was a traumatically extracted. Without any curettage, through the blood flow coming out of the socket, a small yellowish granule was detected and sent for examination. After root-end preparations, the cavities were filled with calcium-enriched mixture cement and the tooth was carefully replanted. Histopathological assessment proved actinomycosis sulfur granule. According to infectious disease specialist recommendation, low-dose and long-term penicillin V was prescribed. Interestingly, at 2-month follow-up, remarkable bone healing was observed. In the cases of apical actinomycosis, IR in combination with antibiotic therapy, even without the curettage of the lesion, may be successfully employed. Keywords: Actinomycosis; Calcium-enriched Mixture; CEM Cement; Endodontic; Tooth Replantation; Periapical Periodontitis